Terrorism and Strategic Effect: a Conceptual Framework - West, Levi J. (Perspectives on terrorism, 2023)
How does terrorism achieve strategic effect? This question has only received limited contemporary consideration despite the expansion and increased sophistication of terrorism studies as a discreet field of inquiry. This article proposes a novel conceptual framework, drawn from the author’s PhD dissertation, that seeks to explain how, and the necessary conditions through which, terrorism is able to achieve strategic effects against its adversaries. The proposed framework argues that three elements must be integrated effectively for the achievement of strategic effect: innovative forms of violence, communicative and narrative dynamics, and the exploitation of emergent information and communications technologies. In detailing these elements, this article also suggests that terrorism retains an enduring nature distinct from the changing character of its specific manifestations. In doing so, the article seeks to contribute to the underdeveloped conceptual literature that informs terrorism studies, as well as the broader literature on asymmetric warfare strategies.